Versatile Microwave Photonic filter based on 100- channel Brillouin Raman fiber laser - Yau, Zhi-Yong; Shee, Yu-Gang; Lim, Eng-Hock; Zhang, Zuxing; Mahdi, Mohd Adzir (Springer Science and Business Media LLC, 2024)
Microwave photonic filters (MPF) are among the most crucial components required for meeting the demands of high-speed and high-frequency signal processing of modern telecommunication systems. For the first time, here, we propose an MPF based on a double wavelength spacing Brillouin-Raman fiber laser (BRFL) to realize a versatile bandpass filter. The proposed setup generated 100 optical taps output with ~ 20 GHz spacings as the light source of the MPF. A dispersive medium of 5 km long single mode fiber and 3.46 km long dispersion compensating fiber were used to characterize the effect of the time delay on the central frequency of the MPF passband. A reconfigurable 3-dB bandwidth from 150 MHz to 1.12 GHz centered around 10.3 GHz is achievable by varying the BRFL optical channel numbers using 10 to 100 optical taps with 20 GHz spacing. The 3-dB bandwidth and Q-factor of the proposed MPF were investigated experimentally and found to be in good agreement with simulation, demonstrating the potential of the BRFL as a laser source for the realization of flexible and versatile radio frequency transversal filters with potentially reduced cost and complexity.